A lightweight convergent personal mobile service delivery approach based on phone book. (13th September 2013) - Qiao, Xiuquan; Xue, Sida; Chen, Junliang; Fensel, Anna
SUMMARY Mobile phone users are demanding an efficient convergent communication approach for efficient communication and information sharing with their real life social circles. Unfortunately, the existing telecom services and the popular Internet services are not organically integrated to provide convenient convergent services. To overcome this issue, one of the promising convergent communication services considered by telecom carriers is RCS (Rich Communication Suite). However, existing issues, such as insufficient interoperability among different operators, shortage of terminals and heavy dependence on large‐scale IP multimedia subsystem (IMS) network deployment, mean that it will take time to implement RCS across worldwide networks and for it to become a service equally universal as voice and short message. Instead of a heavyweight RCS solution, in this paper, we propose a lightweight, quick deployment mobile phone book application system based on cloud computing without a fully deployed IP multimedia subsystem infrastructure, which seamlessly integrates traditional telecommunication services, instant messaging services, social networking services and automatic contact information management. Based on this, 'Telco‐OTT' service provision approach, telecom carriers can allow their subscribers to enjoy conveniently the rich convergent personal service experience quickly without a large initial investment. Thus, it is a low‐risk opportunity for telecom carriers to meet subscriber demand for advanced user‐centric convergent service features. Copyright © 2013 John Wiley & Sons, Ltd.